Developmental Regulation of Amylase Activity During Fruiting of Schizophyllum commune - Schwalb, Marvin N. (1971)
During the development of fruit bodies of Schizophyllum commune there is a minimum 10- to 15-fold increase in amylase activity. There is little or no activity in homokaryons or dikaryons. The activity is found early after the onset of morphogenesis and increases until the fruit bodies are mature. Inhibition studies with CO(2) indicate that the activity is directly associated with fruiting, as a change from fruiting to vegetative growth of the dikaryotic mycelium leads to a loss in activity, whereas the already formed fruit bodies show no loss. The activity is unaffected by the level of glucose in the medium. Evidence is presented, based on the mode of starch degradation and on yield and inhibition studies, that the enzyme is a glucoamylase.